Urban Parterre Modelling UPM: lifting the cadastral map to the third dimension. - Psenner, Angelika; Kodydek, Klaus (My University, 2018)
As conventional cadastral maps only show building perimeters, they contain no information about the city s internal structure about the complex interplay of architecture and its socio-economical use. Thus, urban planning seems to spare little thought for what really takes place inside the buildings lining a street, although we perfectly know that the potentials of ground floor use and the structure of the correlating public street space are directly related. The Urban Parterre Modelling UPM-method refers to the city s parterre as a holistic urban system: it covers both built-up and non-built-up areas. Thus street, ground floor and courtyard are treated as entity, so that their interrelations can come to light. Technically the method represents the merging of a common 3D-city-model and a Comprehensive Ground Plan Survey CGPS a researching technique used in the 1960s until the late 1990s (throughout Europe, but mostly in Italy, France and Switzerland).
Keywords: Stadtplanung; Gebäude; Erdgeschoss; Straßenraum